DESKRIPSI PENILAIAN KOGNITIF DALAM PEMBELAJARAN TEMATIK SISWA KELAS V SD NEGERI 27 PONTIANAK UTARA - Desi Arliyanti; Hery Kresnadi; Suparjan Suparjan (Universitas Tanjungpura, 2021)
AbstractThis research aimed to describe (1)planning (2)implementation and (3)theutilization of cognitive assessment in thematic learning of students in fifth grade ofSDN 27 Pontianak Utara. This research used descriptive research method with aqualitative approach. The subject of the research was the fifth-grade teacher ofSDN 27 Pontianak Utara which consisted of two people. Data collectiontechniques in this research were observation, interviews, and documentation. Dataanalyses in this research were data collection, data reduction, data presentation,and verification/ conclusion drawn. Based on the data analysis, the results are: atthe planning stage, cognitive assessment had generally been carried out in linewith the Assessment Guidelines for Elementary Schools (SD) although there wereshortcomings, there was no technical planning and assessment form; at the stageof implementing cognitive assessment in thematic learning was generally carriedout in accordance with the Assessment Guide for Elementary Schools (SD)although there were shortcomings, namely the absence of problem analysis,besides that the assessment was not carried out face-to-face but questions weredistributed to students for them to perform those at home; and at the stage ofutilizing cognitive assessment in thematic learning, it has not provided remediallyand enrichment for students.Keywords: Cognitive Assessment, Description, Thematic Learning